The Oleaginous Rhodotorula mucilaginosa Isolated from Paddy Field Soils and the Profile of Fatty Acid in Its Intracellular Microbial Oils - Boontanom, Parima; Emnin, Nannaphat; Planonth , Songsak; Chantarasiri, Aiya (Trends in Sciences, 2025)
Oleaginous yeasts are a specific group of yeast species known for their ability to accumulate significant amounts of intracellular microbial oils, also referred to as single-cell oils, which constitute more than 20 % of their dry cell weight. These microbial oils represent a promising resource for various biotechnological and biofuel applications. However, only a few known yeast species have been classified as oleaginous. This study focused on isolating and identifying oleaginous yeasts from the soil in paddy fields across 3 provinces in Thailand. The yeasts that were isolated were assessed for their intracellular lipid accumulation using a quantitative Sudan IV staining and a qualitative weighting method. Among the isolated strains, the one with the highest lipid accumulation was considered for its fatty acid composition using gas chromatography. The results revealed that 6 strains of yeast were isolated from the paddy field soil samples, and these were designated as oleaginous, with intracellular lipid content ranging from 20.41 ± 2.24 to 44.11 ± 3.27 % (w/w). Molecular genetic evaluations indicated that the six strains belonged to the genera Debaryomyces, Meyerozyma, Rhodotorula, and Starmerella. Notably, the R. mucilaginosa strain RYA07 exhibited the highest lipid accumulation, with its intracellular lipids primarily consisting of palmitic acid (C16:0), stearic acid (C18:0), and oleic acid (C18:1n9c). These fatty acids have potential applications in various biotechnological fields, including biodiesel production, food industry, cosmetics, and pharmaceuticals. HIGHLIGHTS Soils from paddy fields collected in 3 provinces of Thailand were used to isolate soil-derived oleaginous yeasts. Six strains of these soil yeasts were identified as oleaginous, each containing more than 20 % (w/w) of intracellular lipids. Some strains of these soil yeasts were newly recorded as oleaginous. Rhodotorula mucilaginosa strain RYA07 was found to accumulate 44.115 % (w/w) of intracellular lipids, which primarily consisted of palmitic acid (C16:0), stearic acid (C18:0), and oleic acid (C18:1n9c). GRAPHICAL ABSTRACT